Relationship between left bundle branch block patterns and super-response to cardiac resynchronization therapy in patients with heart failure - N. E. Shirokov; V. A. Kuznetsov; V. V. Todosiychuk; A. M. Soldatova; D. V. Krinochkin (Российский кардиологический журнал)
Aim. To assess a relationship of left bundle branch block (LBBB) patterns defined by electrocardiography (ECG) and echocardiography with super-response (SR) to cardiac resynchronization therapy (CRT).Material and methods. Sixty patients (mean age, 54,5±10,4 years) were examined at baseline and during follow-up (10,6±3,6 months). Patients were divided into groups: group I (n=31) — decrease of left ventricular end-systolic volume (ESV) ≥30% (super-responders) and II group (n=29) — decrease of LV ESV <30% (non-super-responders). Three strain-markers of LBBB assessed by tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE) were used: early contraction of basal or midventricular segment in the septal wall and early stretching of basal or midventricular segment in the lateral wall (marker 1); early peak contraction of the septal wall occurred in the first 70% of the systolic ejection phase (marker 2, septal flash (SF)); early stretching wall that showed peak contraction after aortic valve closure (marker 3). The classical LBBB pattern was defined if all three strain-markers were present. The heterogeneous LBBB pattern was defined if two from three strain-markers were present.Results. At baseline, groups did not differ in main clinical characteristics, including QRS width and LBBB assessed by ECG. Mechanical abnormalities were found only in group I: SF (32,3% vs 0,0%; p=0,001) and apical rocking (19,4% vs 0,0%; p=0,024), as well as classic LBBB mechanical pattern (20,8% vs 0,0%; p=0,05). The complex of heterogeneous LBBB mechanical pattern (odds ratio (OR), 7,512; 95% CI, 1,434-39,632; р=0,025), interventricular mechanical delay (OR, 1,037; 95% CI, 1,005-1,071; р=0,017) and longitudinal strain of interventricular septum mid segment (OR, 0,726; 95% CI, 0,540-0,977; р=0,035) had an independent relationship with SR. According to the ROC analysis, the sensitivity and specificity of model in SR prediction were 77,3% and 91,3% (AUC=0,862; p<0,001).Conclusion. SR is associated with both LBBB mechanical patterns assessed by STE and TDI. LBBB defined by ECG did not have significant association with SR to CRT.